2021
DOI: 10.1097/ccm.0000000000005168
|View full text |Cite
|
Sign up to set email alerts
|

ABCDEF Bundle Practices for Critically Ill Children: An International Survey of 161 PICUs in 18 Countries*

Abstract: MEASUREMENTS AND MAIN RESULTS:Of the 161 participating PICUs, 83% were in academic teaching hospitals and 42% were in free-standing children's hospitals. Median size was 16 beds (interquartile range, 10-24 beds). Only 15 PICUs (9%) had incorporated all six ABCDEF bundle components into routine practice. Standardized pain assessment (A) was the most common (91%), followed by family engagement (F, 88%) and routine sedation assessment (C) with validated scales (84%). Protocols for testing extubation readiness or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
43
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 51 publications
5
43
0
1
Order By: Relevance
“…In addition, the sedation assessment and delirium elements of the ICU liberation bundle were more commonly present than the ERT and early mobility elements. Although these findings are consistent with recent international practice data, our study adds a more in-depth understanding of international practice relevant to pediatric ventilation liberation and the "B" bundle element (21). These results reinforce an opportunity to standardize pediatric ventilation practices in an effort to eliminate noise and discriminate strategies that drive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the sedation assessment and delirium elements of the ICU liberation bundle were more commonly present than the ERT and early mobility elements. Although these findings are consistent with recent international practice data, our study adds a more in-depth understanding of international practice relevant to pediatric ventilation liberation and the "B" bundle element (21). These results reinforce an opportunity to standardize pediatric ventilation practices in an effort to eliminate noise and discriminate strategies that drive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…For children, a recent survey showed an implementation of all aspects in only 9% of 161 PICUs in the US, Canada, Brazil and Europe ( 19 ). Although there are calls for implementation of these measures in pediatric intensive care, as with most medical developments, the use of adult therapies in children without crucial changes beyond adaptation for size and body weight has not been effective ( 18 ).…”
Section: Resultsmentioning
confidence: 99%
“…In 2019, Arroyo-Nonoa et al ( 41 ) found only 8 works on IWS in adult critical care patients, with two published between 1998 and 2016 and 6 between 2017 and 2019. In contrast, this is one aspect where pediatric research is more advanced, having introduced and validated scoring tools for early detection ( 42 , 43 ), after showing it to lead to relevant stress for both patients and parents ( 19 ). Additionally, IWS has been shown to be an independent risk factor for development of delirium, which in turn factors heavily within the long-term effects of critical care treatment (see bundle D below).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations